Friction and wear behavior of WC-Ni coatings HVOF sprayed on duplex stainless steel. Issue 1 (February 2020) - Xu, H S; Dong, Q
Abstract: The friction and wear behavior of high-velocity oxygen-fuel (HVOF) sprayed WC-Ni coatings was investigated. WC-Co coating was used as reference sample. Pin-on-disc tests were conducted on WC-Ni and WC-Co coatings surface in both pure water and 3.5% (wt.) saline solution, respectively. It was found that WC-Co coatings has superior wear and corrosion resistance in pure water due to their high hardness. However, cracks were observed in the wear scar of WC-Co coating, which wear rate was 2-4 times higher than that of WC-Ni coatings. The corrosion-wear resistance is not only affected by coating hardness, but also by powder composition. So WC-CrNi coating displays an excellent wear-and corrosion-resistance performance in saline solution.